MNE as a catalyst for field-level institutional change in the Russian bakery sector. Issue 4 (11th November 2019) - Pelto, Elina; Karhu, Anna
Abstract : Purpose: The purpose of this paper is to focus on analysing how foreign entry by a multinational enterprise (MNE) can act as a catalyst for change in field-level institutional logics in a transition economy context. Design/methodology/approach: The paper presents an empirical single-case study on the effects of an MNE's entry on a particular industry in an emerging market's context. The empirical study follows abductive reasoning; based on the interplay of previous literature and empirical observations, it identifies mechanism through which MNEs can catalyse change in field-level institutional logics. Findings: The study shows that in addition to general market transition influenced by state-level policies, individual companies' strategies, actions and market behaviour also significantly contribute to the development of a host industry's field-level institutional logics. More precisely, a case study of a Finnish MNE's entry into the Russian bakery market identifies the mechanisms and various change pathways through which the entry of a single MNE into a transition economy can significantly alter the institutional logics of a particular industry. Originality/value: The study employs a novel perspective that incorporates the ideas, concepts and insights of an institutional logics perspective to MNE entry research for empirical analysis and theory building.